EVALUATING POETRY WRITING INSTRUCTION THROUGH THE PORTOFOLIO APPROACH: A LITERATURE REVIEW - Saidah; Supriyana, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study explores the effectiveness of the portfolio approach in poetry writing instruction through a comprehensive literature review. The research aims to demonstrate how this formative, process-oriented assessment method aligns with contemporary literacy pedagogy that emphasizes creativity, reflection, and learner autonomy. Drawing on peer-reviewed journal articles, academic books, and conference proceedings published between 1985 and 2024, the study employed qualitative content analysis to synthesize theoretical frameworks and empirical findings. Results indicate that portfolio assessment supports three key aspects of poetry instruction: facilitating the creative writing process, enhancing student engagement through reflective learning, and enabling authentic assessment that fosters self-efficacy. By documenting students’ progress from initial ideas to final drafts, portfolios encourage metacognitive awareness and active involvement in learning. The study contributes to the field of Indonesian Language and Literature Education by proposing a conceptual model and offering practical recommendations for implementing portfolio-based pedagogy in poetry writing classrooms. Ultimately, this paper supports the integration of more holistic and student-centered assessment practices that cultivate literary appreciation and writing competence